Improving Sustainable Development Mechanisms Of Flexible Textile Enterprises - Hayitov, Sherzod Pardaboevich (The American Journal of Management and Economics Innovations, 2021)
The issue of improving the mechanisms to ensure the sustainable development of textile enterprises on the basis of a flexible management system has been studied.